Our experience in the diagnosis and treatment of peripheral exudative hemorrhagic chorioretinopathy - I. O. Nasinnyk; G. V. Levytska; M. M. Umanets (Journal of Ophthalmology)
Purpose: To present our experience in the examination and treatment of patients with peripheral exudative hemorrhagic chorioretinopathy (PEHCR).